Lithium fluoroferrite repair material as well as preparation method and application thereof
The lithium radon repair material prepared through the water heat method is doped with the waste Lifepo4 positive pole material, which solves the problem of high -influence electrical performance of the abandoned LIFEPO4 orthopedic material DCR, and realizes the improvement of electrical properties.
Patent Information
- Application Number
- CN202411503670.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The waste LiFePO4 positive electrode material has a high DC internal resistance (DCR) due to repeated charge and discharge, which affects the performance of lithium-ion batteries. The existing repair technology has insufficient process flow and high-salt wastewater production.
Use lithium fluorite repair material to prepare through the water heat method, control the reaction conditions to obtain a uniform and small powder particles, high -purity lithium fluorine fluorine repair materials, and then mix it with the abolished Lifepo4 positive pole material, and mix it through the burning treatment. Miscellaneous repair.
Reduce the DCR of LifePO4 positive materials, improve the ionic conductivity, improve the electrical performance, and restore the electrical properties of waste materials to a certain extent.
Smart Images

Figure CN119370894A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery positive electrode material repair, and in particular to a lithium fluoroferrate repair material and a preparation method and application thereof. Background Art
[0002] In LiFePO4 batteries, the cathode material is the core component, and its cost accounts for about 40-50% of the entire battery. So far, the main methods for recycling and disposing of waste LiFePO4 cathode materials are repair and regeneration and hydrometallurgy. Hydrometallurgy refers to the recovery of a single metal salt product or regeneration into cathode materials through acid leaching and precipitation. It has the advantages of high production efficiency and excellent products, but it has the disadvantages of long process flow and large amount of high-salt wastewater. Repair and regeneration usually uses lithium tempering, chemical or physical means to repair the structure of the material. It has the advantages of simple process flow and low production cost. It is a major research hotspot for the recycling of waste LiFePO4 cathode materials.
[0003] For waste LiFePO4 positive electrode materials, due to repeated charge and discharge during the previous service period, the material generally has a high direct current internal resistance (DCR) defect, so when it is reused, there is a large resistance for ions to migrate to the surface and enter the electrolyte or conductive agent, which seriously affects the performance of lithium-ion batteries. At present, the most direct and effective way to reduce DCR is to regulate the number and size of ion diffusion channels by doping elements with different ion radii, and to regulate the properties of the space charge layer at the interface by interface modification or enrichment of interface elements, so as to improve the ion conductivity, thereby reducing the transmission resistance of ions or electrons. Among them, fluorinated lithium salts are attracting more and more researchers' attention due to the strong charge delocalization and ion dissociation of fluorine. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide a lithium fluoroferrate repair material and its preparation method and application, so as to solve the problem of high DCR affecting the electrical properties of the material that is common in the existing waste LiFePO4 positive electrode material repair technology.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention first provides a method for preparing a lithium fluoroferrate repair material, which comprises the following steps:
[0007] S1. A hydrofluoric acid solution and deionized water were added to the reactor, and a lithium source and an iron source were sequentially added to the reactor, stirred, and heated for a hydrothermal reaction;
[0008] S2. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain lithium fluoroferrate repair material.
[0009] The present invention uses hydrofluoric acid solution, lithium source and iron source as raw materials to prepare lithium fluoroferrate repair material by hydrothermal method, and can accurately control the reaction conditions so that the particle size distribution of the powder particles is more uniform and the particles are finer. The prepared lithium fluoroferrate repair material has high purity and good crystallinity and is easy to be subsequently doped and repaired with waste LiFePO4 positive electrode materials.
[0010] As a further improvement of the above scheme of the present invention, in step S1, the added amounts of the fluorine source, lithium source and iron source satisfy that the molar ratio of fluorine element, lithium element and iron element is 16:6 to 8:3.
[0011] As a further improvement of the above scheme of the present invention, in step S1, the lithium source is one of lithium carbonate and lithium hydroxide; and / or the iron source is one of ferrous chloride and ferrous sulfate.
[0012] As a further improvement of the above solution of the present invention, in step S1, the stirring time is 15 to 25 minutes and the speed is 100 to 400 r / min.
[0013] As a further improvement of the above scheme of the present invention, in step S1, the temperature of the hydrothermal reaction is 180° C. to 220° C., and the time is 10 to 15 hours.
[0014] As a further improvement of the above scheme of the present invention, in step S2, the washing is performed by filtering and washing with pure water for several times.
[0015] As a further improvement of the above scheme of the present invention, in step S2, the drying is carried out at 180° C. to 220° C. under oxygen conditions for 8 to 16 hours.
[0016] The present invention also provides a lithium fluoroferrate repair material, which is prepared by the preparation method of the lithium fluoroferrate repair material as described above.
[0017] The present invention also provides a use of the lithium fluoroferrate repair material as described above in repairing waste LiFePO4 positive electrode materials.
[0018] As a further improvement of the above scheme of the present invention, it includes the following steps: mixing the carbon-containing LiFePO4 material separated from the waste positive electrode sheet with the lithium fluoroferrate repair material to obtain a repaired LiFePO4 positive electrode material; in the repaired LiFePO4 positive electrode material, the content of the lithium fluoroferrate repair material is 0.5wt% to 1wt%.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention uses hydrofluoric acid solution, lithium source and iron source as raw materials to prepare lithium fluoroferrate repair material by hydrothermal method, and can accurately control the reaction conditions, so that the particle size distribution of the powder particles is more uniform, the particles are finer, the prepared material has high purity and good crystallization, and the prepared lithium fluoroferrate repair material has high purity and good crystallization, which is easy to be subsequently doped and repaired with waste LiFePO4 positive electrode materials.
[0021] 2. When the lithium fluoroferrate repair material prepared by the present invention is used to dope and repair waste LiFePO4 positive electrode materials, the doping of fluorine atoms can regulate the number and size of ion diffusion channels, and the properties of the space charge layer at the interface can be regulated by interface modification or interface element enrichment, so that the ion conductivity is improved, thereby reducing the transmission resistance of ions or electrons; at the same time, the lithium element in the lithium fluoroferrate can also supplement lithium, play a role in lithium supplementation and repair to improve electrical properties, thereby reducing the DCR of the LiFePO4 positive electrode material, and the electrical properties of the LiFePO4 positive electrode material can be restored and improved to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a stacking diagram of the lithium fluoroferrate repair material prepared in Example along the c-axis;
[0023] Figure 2 This is a SEM image of the LiFePO4 positive electrode material after lithium fluoroferrate doping and repair prepared in Example;
[0024] Figure 3 It is a DCR comparison curve of the LiFePO4 positive electrode material of the embodiment and the comparative example. DETAILED DESCRIPTION
[0025] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0027] Example 1
[0028] The present embodiment provides a lithium fluoroferrate repair material, and the preparation method thereof includes the following steps: using a pipette to transfer 16 mol of hydrofluoric acid solution and adding it to a hydrothermal reactor, adding an appropriate amount of deionized water to the hydrothermal reactor; then weighing 3 mol of lithium carbonate and slowly adding it to the hydrothermal reactor, bubbles are generated; then weighing 3 mol of ferrous sulfate into the hydrothermal reactor; adding a magnet to the raw materials and stirring the reaction at 100 r / min under a magnetic stirrer, then heating the hydrothermal reactor to 180°C and reacting for 10 hours; after the reaction is completed, the hydrothermal reactor is naturally cooled to room temperature, and then the hydrothermal reactor is opened, the reaction product is filtered and washed with pure water 4 times, and then dried under oxygen conditions at 200°C, and the obtained white powder product is the lithium fluoroferrate repair material.
[0029] This embodiment also uses the above-mentioned lithium fluoroferrate repair material to repair the waste LiFePO4 positive electrode material to obtain the repaired LiFePO4 positive electrode material. The specific repair method is: according to a doping ratio of 0.5%, the prepared lithium fluoroferrate powder and the carbon-containing LiFePO4 positive electrode material separated from the waste positive electrode sheet are fully mixed using a high-speed mixer, and then sent into a tubular furnace under a nitrogen atmosphere and calcined at 650°C for 6 hours to obtain the LiFePO4 positive electrode material doped and repaired with lithium fluoroferrate.
[0030] Example 2
[0031] The present embodiment provides a lithium fluoroferrate repair material, and the preparation method thereof includes the following steps: pipetting 16 mol of hydrofluoric acid solution into a hydrothermal reactor, adding an appropriate amount of deionized water into the hydrothermal reactor; weighing 6 mol of lithium hydroxide and slowly adding it into the hydrothermal reactor to generate bubbles; then weighing 3 mol of ferrous chloride into the hydrothermal reactor; adding a magnet to the raw material and stirring the reaction at 100 r / min under a magnetic stirrer, then heating the hydrothermal reactor to 180° C. and reacting for 10 hours; after the reaction is completed, the hydrothermal reactor is naturally cooled to room temperature, then the hydrothermal reactor is opened, the reaction product is filtered and washed with pure water 4 times, and then dried under oxygen conditions at 200° C., and the obtained white powder product is the lithium fluoroferrate repair material.
[0032] This embodiment also uses the above-mentioned lithium fluoroferrate repair material to repair the waste LiFePO4 positive electrode material to obtain the repaired LiFePO4 positive electrode material. The specific repair method is: according to a doping ratio of 0.5%, the prepared lithium fluoroferrate powder and the carbon-containing LiFePO4 positive electrode material separated from the waste positive electrode sheet are fully mixed using a high-speed mixer, and then sent into a tubular furnace under a nitrogen atmosphere and calcined at 650°C for 6 hours to obtain the LiFePO4 positive electrode material doped and repaired with lithium fluoroferrate.
[0033] Example 3
[0034] The present embodiment provides a lithium fluoroferrate repair material, and the preparation method thereof includes the following steps: pipetting 16 mol of hydrofluoric acid solution into a hydrothermal reactor, adding an appropriate amount of deionized water into the hydrothermal reactor; weighing 3 mol of lithium carbonate and slowly adding it into the hydrothermal reactor to generate bubbles; then weighing 3 mol of ferrous sulfate into the hydrothermal reactor; adding a magnetic particle to the raw material and stirring the reaction at 400 r / min under a magnetic stirrer, then heating the hydrothermal reactor to 220° C. and reacting for 10 hours; after the reaction is completed, the hydrothermal reactor is naturally cooled to room temperature, and then the hydrothermal reactor is opened, the reaction product is filtered and washed with pure water 4 times, and then dried under oxygen conditions at 200° C., and the obtained white powder product is the lithium fluoroferrate repair material.
[0035] This embodiment also uses the above-mentioned lithium fluoroferrate repair material to repair the waste LiFePO4 positive electrode material to obtain the repaired LiFePO4 positive electrode material. The specific repair method is: according to a 1% doping ratio, the prepared lithium fluoroferrate powder and the carbon-containing LiFePO4 positive electrode material separated from the waste positive electrode sheet are fully mixed using a high-speed mixer, and then sent into a tubular furnace under a nitrogen atmosphere and calcined at 650°C for 6 hours to obtain the lithium fluoroferrate doped and repaired LiFePO4 positive electrode material.
[0036] Example 4
[0037] The present embodiment provides a lithium fluoroferrate repair material, and the preparation method thereof includes the following steps: pipetting 16 mol of hydrofluoric acid solution into a hydrothermal reactor, adding an appropriate amount of deionized water into the hydrothermal reactor; weighing 6 mol of lithium hydroxide and slowly adding it into the hydrothermal reactor to generate bubbles; then weighing 3 mol of ferrous chloride into the hydrothermal reactor; adding a magnet to the raw material and stirring the reaction at 400 r / min under a magnetic stirrer, then heating the hydrothermal reactor to 220° C. and reacting for 10 hours; after the reaction is completed, the hydrothermal reactor is naturally cooled to room temperature, then the hydrothermal reactor is opened, the reaction product is filtered and washed with pure water 4 times, and then dried under oxygen conditions at 200° C., and the obtained white powder product is the lithium fluoroferrate repair material.
[0038] This embodiment also uses the above-mentioned lithium fluoroferrate repair material to repair the waste LiFePO4 positive electrode material to obtain the repaired LiFePO4 positive electrode material. The specific repair method is: according to a 1% doping ratio, the prepared lithium fluoroferrate powder and the carbon-containing LiFePO4 positive electrode material separated from the waste positive electrode sheet are fully mixed using a high-speed mixer, and then sent into a tubular furnace under a nitrogen atmosphere and calcined at 650°C for 6 hours to obtain the lithium fluoroferrate doped and repaired LiFePO4 positive electrode material.
[0039] Comparative Example
[0040] This comparative example uses unrepaired carbon-containing LiFePO4 positive electrode material separated from waste positive electrode sheets.
[0041] Test Case
[0042] The crystals of lithium fluoroferrate powder prepared in Example 3 were recorded using a Bruker SMART APEX II crystal diffractometer at room temperature to determine the single crystal structure. The stacking diagram of the single crystal structure along the c-axis is shown in FIG. Figure 1 As shown, brown represents iron atoms, silver represents lithium atoms, red represents oxygen atoms, and green represents fluorine atoms.
[0043] The LiFePO4 cathode material prepared in Example 3 after repair by lithium fluoride ferrate doping was tested and analyzed using a Zeiss Sigma 300 desktop scanning electron microscope at a voltage of 1 kV to obtain a 20000x SEM image. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that doping does not change the normal morphology of lithium iron phosphate and does not cause any damage.
[0044] The LiFePO4 positive electrode material doped and repaired with lithium fluoride prepared in Example 3 and the unrepaired carbon-containing LiFePO4 positive electrode material of the comparative example were tested using the test method mentioned in IEC-61960-2003, I1=0.2C, I2=1C; I1 was used to discharge for 10s and record the voltage U1, and the discharge current value I2 was instantly increased, and the discharge was performed for 1s, and the voltage U2 was recorded; the DCR shown in different SOC states is different. Generally, multiple points are selected for comparison during material evaluation. The results are shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that under different states of charge (SOC), the DCR of the doped and repaired LiFePO4 is significantly reduced, and the doping and repair effect is obvious.
[0045] The LiFePO4 positive electrode materials of Examples 1-4 and the comparative example were respectively prepared into lithium batteries: the negative electrode was a graphite negative electrode, the electrolyte was a pp diaphragm (polypropylene diaphragm), and the mass ratio of positive electrode material: negative electrode material: electrolyte was 6:3:1.
[0046] The prepared batteries were subjected to cycle performance tests, the test methods being as follows: (1) at 60°C, the battery was cycled 1000 times at a charge and discharge rate of 0.2C under a load voltage of 3.2V (using Blue Power lithium battery charge and discharge test equipment CT6002A). The capacity retention rate is shown in Table 1; (2) at 60°C, the battery capacity was tested at a discharge rate of 0.2C under a load voltage of 3.2V. The results are shown in Table 2.
[0047] Table 1
[0048]
[0049] Table 2
[0050]
[0051] It can be seen from the results in Tables 1 and 2 that compared with undoped waste LiFePO4, the electrical properties of the LiFePO4 positive electrode material repaired with lithium fluoroferrate are significantly improved. At the same time, when lithium carbonate is used as the lithium source, the repair temperature is 220°C, and the doping ratio is 1%, the repaired LiFePO4 has the best electrical performance, the cycle capacity retention rate can reach 93.15%, and the 0.2C discharge capacity reaches 165.32mAh / g.
[0052] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0053] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium fluoroferrate repair material, characterized in that: It includes the following steps: S1. A hydrofluoric acid solution and deionized water were added to the reactor, and a lithium source and an iron source were sequentially added to the reactor, stirred, and heated for a hydrothermal reaction; S2. After the reaction is completed, cool to room temperature, filter, wash and dry to obtain lithium fluoroferrate repair material.
2. The method for preparing the lithium fluoroferrate repair material according to claim 1, characterized in that: In step S1, the added amounts of the fluorine source, lithium source and iron source satisfy the following conditions: the molar ratio of fluorine element, lithium element and iron element is 16:6 to 8:
3.
3. The method for preparing the lithium fluoroferrate repair material according to claim 1, characterized in that: In step S1, the lithium source is one of lithium carbonate and lithium hydroxide; and / or the iron source is one of ferrous chloride and ferrous sulfate.
4. The method for preparing the lithium fluoroferrate repair material according to claim 1, characterized in that: In step S1, the stirring time is 15 to 25 minutes and the speed is 100 to 400 r / min.
5. The method for preparing the lithium fluoroferrate repair material according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal reaction is 180°C to 220°C, and the time is 10 to 15 hours.
6. The method for preparing the lithium fluoroferrate repair material according to claim 1, characterized in that: In step S2, the washing is performed by filtering and washing with pure water for several times.
7. The method for preparing the lithium fluoroferrate repair material according to claim 1, characterized in that: In step S2, the drying is carried out at 180°C to 220°C under oxygen conditions for 8 to 16 hours.
8. A lithium fluoride ferrate repair material, characterized in that: The lithium fluoroferrate repair material is prepared by the preparation method of the lithium fluoroferrate repair material as described in any one of claims 1 to 7.
9. Use of the lithium fluoroferrate repair material as claimed in claim 8 in repairing waste LiFePO4 positive electrode materials.
10. The use according to claim 9, characterized in that: It includes the following steps: The carbon-containing LiFePO4 material separated from the waste positive electrode sheet is mixed with the lithium fluoroferrate repair material to obtain a repaired LiFePO4 positive electrode material; in the repaired LiFePO4 positive electrode material, the content of the lithium fluoroferrate repair material is 0.5wt% to 1wt%.